Posthuman Ecological Concerns in the Select Works of Ruskin Bond: A Critical Study - Sukanya Jalihal (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
The immediacy to develop the posthuman concerns/approaches towards the depleting ecology, calls for a convergence of literary narratives to stimulate the human mind towards ecological conservation. There has been an undeclared environmental emergency that needs to be addressed at the earliest in the wake of global warming. Ruskin Bond’s short stories portray the need to develop an amicable relation with the nature and its profundities in the era of plastics & its horrific effects on the environment. Banyan trees, oak, pine trees, blue sky, pristine rivers, globules of nectar, fragrance of fallen pine needles, shiny grass, chilly mountain streams, the majestic Himalayas, all find place in the literary portrait of Bond. Technological advancement has robbed the nature of its purity, and has exposed the mankind to the dangers of extinction. Bond’s short stories reverberate the concern for the ecology and underlines the dependence of humans on the nature. The Cherry Tree, Dust on the Mountain, Time stops at Shamli, Tiger, Tiger Burning bright, and other short stories contain the beauty of flora and fauna and instils a strong urge to preserve the nature for the mankind’s survival. This paper aims at establishing the importance of re-reading Ruskin Bond, since planet earth is in a precarious condition. It is time to adopt a posthuman approach towards the ecology and harness the nature for the human need, and not for greed. The bio technological developments, such as synthetic intelligence, robotics, genetic modification, and bio-engineering, etc. have insinuated dystopian condition filled with anxieties about a human existence. Bond’s short stories are a consolation and brings a ray of hope to the tattered souls.